PENGARUH IMPOR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Muhamad Subhan; M. Yunus; Robi Agustin (Program Studi Ekonomi Syariah, 2021)
Economic growth is a measure of the progress of an economic movement. Islamic economic growth has existed during the dialogue of classical Muslim thought, namely the so-called